Rewards, knowledge sharing and individual work performance: an empirical study - Nam Nguyen Kim; Nga Nguyen Thi Hang (Cogent Business & Management, 2024)
The banking industry is currently striving to adapt to the rapid development of technology, creating competitive advantages through knowledge management activities. This study investigates the impact of rewards on knowledge sharing behavior and its subsequent influence on individual work performance within the banking sector. The research involves analyzing 263 survey responses from employees working in both private and public sector banks. We employ a linear structural model to evaluate the proposed research hypotheses using SPSS and AMOS 20 software. This study shows that rewards solely affect the explicit knowledge sharing. Moreover, both tacit and explicit knowledge sharing significantly and positively contribute to individual work performance. Additionally, the study uncovers the mediating role of explicit knowledge sharing in the relationship between rewards, tacit knowledge sharing, and individual work performance. This study holds significant implications for managers in the banking sector when designing reward systems to foster knowledge sharing (both tacit and explicit) and individual work performance within the organization, particularly in Vietnam.Knowledge management is becoming increasingly important in knowledge-intensive industries such as banking. This study provides evidence of the relationship between rewards and knowledge sharing behavior in the banking sector in Vietnam. Furthermore, knowledge sharing among employees within an organization contributes to the enhancement of individual work performance. With these findings, the article offers deeper insights into the construction of a reward system in the banking sector to stimulate knowledge-sharing activities and improve individual work performance.
Keywords: 650; banking; Explicit knowledge; performance; share; tacit knowledge